2012
DOI: 10.7860/jcdr/2012/4865.2627
|View full text |Cite
|
Sign up to set email alerts
|

Blood Lead in End-Stage Renal Disease (ESRD) Patients who were on Maintainence Haemodialysis

Abstract: Background: In India, there is rising burden of chronic diseases like hypertension and diabetes. It has been estimated that 25-40% of these patients are likely to develop CKD, with a significant percentage requiring renal replacement therapy. Haemodialysis is the most common method which is used to treat advanced and permanent kidney failure. The derangements in the metabolism of several toxic and trace elements such as antimony, arsenic, cadmium, molybdenum, nickel, and selenium have been reported for several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…ESRD leads to accumulation of certain toxic elements, which affects normal functions of the body, and may have significant complications including cardiovascular disease, immune deficiency, anemia, renal function impairment, and bone disease. [ 85 ] Xerostomia was found in 28-59% of ESRD patients due to inability of kidneys to reabsorb sodium and the resultant polyuria. [ 86 87 ]…”
Section: Resultsmentioning
confidence: 99%
“…ESRD leads to accumulation of certain toxic elements, which affects normal functions of the body, and may have significant complications including cardiovascular disease, immune deficiency, anemia, renal function impairment, and bone disease. [ 85 ] Xerostomia was found in 28-59% of ESRD patients due to inability of kidneys to reabsorb sodium and the resultant polyuria. [ 86 87 ]…”
Section: Resultsmentioning
confidence: 99%
“…However, the mean lead level in hemodialysis patients was higher than the international standard level. Previous studies showed a higher lead level in hemodialysis patients than healthy people (15).…”
Section: Discussionmentioning
confidence: 89%
“…Palaneeswari et al studied 100 hemodialysis patients to measure the serum lead level and its relationship with hemodialysis duration. They found that serum lead level slightly increased with the increases in the duration of hemodialysis session (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ESRD represents a progressive clinical condition in which an irreversible loss of endogenous renal function below a sufficient degree is established, imposing permanent dependency on renal replacement therapy (RRT) to avoid life-threatening uremia and other complications. Treatment of this disease is affected through RRT, including peritoneal dialysis (PD), hemodialysis (HD), or kidney transplantation (KT) (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%